2010
DOI: 10.1165/rcmb.2009-0144oc
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Factor Pathway Inhibitor Overexpression Inhibits Hypoxia-Induced Pulmonary Hypertension

Abstract: Pulmonary hypertension (PH) is a commonly recognized complication of chronic respiratory disease. Enhanced vasoconstriction, pulmonary vascular remodeling, and in situ thrombosis contribute to the increased pulmonary vascular resistance observed in PH associated with hypoxic lung disease. The tissue factor pathway regulates fibrin deposition in response to acute and chronic vascular injury. We hypothesized that inhibition of the tissue factor pathway would result in attenuation of pathophysiologic parameters t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 53 publications
1
23
0
Order By: Relevance
“…A mouse overexpressing tissue factor pathway inhibitor (TFPI) was found to have reduced pulmonary hypertension when exposed to hypoxia [50]. We have recently shown that pharmacological inhibition of FXa by the direct, selective inhibitor rivaroxaban is beneficial in the MCT model of experimental pulmonary hypertension [6].…”
Section: Discussionmentioning
confidence: 99%
“…A mouse overexpressing tissue factor pathway inhibitor (TFPI) was found to have reduced pulmonary hypertension when exposed to hypoxia [50]. We have recently shown that pharmacological inhibition of FXa by the direct, selective inhibitor rivaroxaban is beneficial in the MCT model of experimental pulmonary hypertension [6].…”
Section: Discussionmentioning
confidence: 99%
“…Heterozygous mTFPI ΔK1 deficiency also increases neointimal proliferation in the murine model of flow cessation-induced vascular remodeling (170). On the other hand, over expression of mTFPIα (the isoform only present in the platelets of adult mice) in vascular smooth muscle cells limits ferric chloride induced carotid artery occlusion (171), reduces the smooth muscle cell proliferation and pulmonary vascular remodeling induced by chronic hypoxia (172), and unexpectedly lowers plasma cholesterol levels and atherosclerotic plaque development in the apoE knock-out model of atherosclerosis (173). …”
Section: In Micementioning
confidence: 99%
“…TFPI expression is increased locally in vascular smooth muscle cells, but also at the endothelial surface, as evidenced by increased heparin-releasable TFPI and systemically, with raised plasma TFPI antigen levels. 18 Heparin-releasable TFPI must come from the intravascular, endothelial surface. We demonstrated a clear inhibition of angiogenesis in recovery from hind-limb ischemia in these mice.…”
Section: Discussionmentioning
confidence: 99%
“…17 These mice (in C57Bl/6 background) have increased vascular expression of full-length murine TFPI. 18 Male, age-matched C57Bl/6 mice were used as controls in all experiments.…”
Section: Methodsmentioning
confidence: 99%